2011
DOI: 10.19030/ijmis.v14i2.832
|View full text |Cite
|
Sign up to set email alerts
|

Trust In Personal And Impersonal Forms Its Antecedents And Consequences: A Conceptual Analysis Within Organizational Context

Abstract: Although Mayer et al.'s (1995) Luhman (1979), McCauley & Kuhnert (1992), Zaheer et al.(1998), Costigan et al.(1998), McKnight et al.(1998McKnight et al.( ,2002, and Atkinson and Butcher( 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 100 publications
0
9
0
1
Order By: Relevance
“…Trustworthiness, on the other hand, involves the ability, benevolence and integrity of a trustee [30,31]. Some scholars view trust as synonymous with trustworthiness and explain trust in the context of personal attributes that impel positive expectations on the part of the trustee [32,33].…”
Section: Definition Of Trustmentioning
confidence: 99%
“…Trustworthiness, on the other hand, involves the ability, benevolence and integrity of a trustee [30,31]. Some scholars view trust as synonymous with trustworthiness and explain trust in the context of personal attributes that impel positive expectations on the part of the trustee [32,33].…”
Section: Definition Of Trustmentioning
confidence: 99%
“…De acordo com Oliveira e Souza (2014), a produção científi ca sobre confi ança no âmbito organizacional tem crescido nos últimos anos, o que pode ser ilustrado com alguns estudos que relacionam este construto a variáveis tais como gestão organizacional (Drummond, 2007;Novelli, Fischer, & Mazzon, 2006;Reina & Reina, 2007); comportamento cooperativo (Ferrin et al, 2007) e comprometimento organizacional (Chhetri, 2014;Song & Kim, 2009); cidadania organizacional (Cavazotte et al, 2013;Chhetri, 2014;Hakim et al, 2014;Hassan & Semerciöz, 2010); satisfação no trabalho (Hakim et al, 2014;Leat & El-Kot, 2009); e valores pessoais e organizacionais (Oliveira & Souza, 2014).…”
Section: Valores E Confi Ança Organizacionais: Fatores Determinantes unclassified
“…This is a facet that was laid out in detail by Mechanic's research (1996) of trust and the differences in trust presented by cultural and sociological differences. Hassan and Semerciöz (2010) showed that an individual's trust was based on a variety of influencing factors such as individual personality traits, cultural characteristics, and past experiences.…”
Section: Trust and Trustworthinessmentioning
confidence: 99%